BENTUK PARTISIPASI MASYARAKAT DALAM KEGIATAN POSYANDU KASIH IBU - Essy Ena Lestari; Agus Zainal Rachmat (UNIB Press, Universitas Bengkulu, 2021)
This study aims to describe the form of community participation in the activities of the Ibu Jaya Posyandu Kasih Ibu Village, Sumber Jaya Village, Kampung Melayu District, Bengkulu City. This study used a qualitative descriptive study with interview, observation, and documentation methods. Checking the validity of the data used triangulation, namely time triangulation, subject triangulation, and technical triangulation. The results showed that there are forms of community participation in the activities of Posyandu Kasih Ibu, Sumber Jaya Village, Kampung Melayu District, Bengkulu City, namely: 1) Money participation. Community voluntary contributions for mutual assistance during maternal and child health activities (KIA), and diarrhea prevention and control activities at the Kasih Ibu Posyandu, 2) Participation of personnel. The community helps cadres in the Kasih Ibu Posyandu, for the purpose of providing maternal and child health services. For example, helping weigh the baby, cleaning up the Posyandu after the activity, etc., and 3) Participation skills. The community is skilled at making ORS, which are given to mothers and children in the prevention and control of diarrhea at the Kasih Ibu Posyandu.